Comparison of the Effectiveness of Mindfulness-Based Stress Reduction Group Exercises with Emotion-Focused Group Therapy on Authentic Happiness in Critically Ill Inpatients and Recovered COVID-19 Patients - Hatami, Samaneh; Khakpour, Masoud; Saffarian, Mohamadreza (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to compare the effectiveness of Mindfulness-Based Stress Reduction (MBSR) group exercises and Emotion-Focused Group Therapy (EFGT) on the authentic happiness of critically ill inpatients and those recovered from COVID-19.Methods: The research utilized a quasi-experimental design with three groups (one control group and two experimental groups), conducted in three phases (pre-test, post-test, and three-month follow-up). The study population included all critically ill patients hospitalized and then recovered from COVID-19 during the second quarter of 2021 at Imam Reza Hospital in Mashhad. A sample size of 15 patients per group, totaling 45 patients, was considered. Patients were randomly assigned to three groups using a convenience sampling method. The training group (1) received eight 45-minute sessions of Emotion-Focused Group Therapy by Greenberg, Warwar, and Malcolm (2008), and training group (2) underwent eight 120-minute sessions of MBSR by Kabat-Zinn (2005), while the control group did not receive any treatment. Data were collected using Rashid's (2008) Authentic Happiness Inventory and analyzed using mixed ANOVA with repeated measures through SPSS-23 software.Findings: Results indicated that although both treatments had an effect on authentic happiness and its components up to the follow-up stage (p < 0.01), no significant difference in the effectiveness of the two treatments on authentic happiness in patients was observed.Conclusion: This research could broadly benefit the psychological state improvement in critically ill inpatients and those recovering from acute or chronic illnesses.